Differences in Early Adult Anxiety during COVID-19 Pandemic: Analysis Rasch Model - Meylia Sari (Psychocentrum Review, 2021)
Since COVID-19 pandemic entered Indonesia, mental health experts have also investigated the increase in psychological problems, one of which is anxiety. The fear of being infected or unknowingly infecting other people is a major source of anxiety during COVID-19 pandemic. This study aims to describe the differences in early adult anxiety during COVID-19 in terms of gender. This study is a comparative study at the early adult development stage in Indonesia, obtained through random sampling. The sample of this study was 206 people (male = 66; female = 140). The analysis technique used is the Welch Test on the Rasch model with the help of WINSTEPS Version 3.73. The analysis showed that there was no difference in anxiety during COVID-19 between male and female early adulthood. This condition is caused by early adulthood male and female depending on the internet and smartphones to find information when quarantining at home, increasing feelings of anxiety about being infected with COVID-19. The implementation of guidance and counseling is discussed further